2002
DOI: 10.1016/s1010-7940(01)00990-3
|View full text |Cite
|
Sign up to set email alerts
|

Extensive use of polytetrafluoroethylene artificial grafts for prolapse of bilateral mitral leaflets

Abstract: Because replacement of artificial chordae was not complicated and seemed to preserve fine relationships among leaflet tissues, chordae, and papillary muscles, we therefore suggest that the extensive use of PTFE artificial chordae appears to be a promising procedure for the repair of all kinds of mitral lesions causing mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…We reconfirmed that PTFE sutures are suitable for an artificial chordae repair and for an extended operative application for a BML prolapse, and we started to use this technique as the initial treatment for AML prolapse in 1991. Our results show the chordal replacement technique to be applicable for the repair of all types of BML prolapse, 11 AML prolapse, and PML prolapse.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…We reconfirmed that PTFE sutures are suitable for an artificial chordae repair and for an extended operative application for a BML prolapse, and we started to use this technique as the initial treatment for AML prolapse in 1991. Our results show the chordal replacement technique to be applicable for the repair of all types of BML prolapse, 11 AML prolapse, and PML prolapse.…”
Section: Discussionmentioning
confidence: 78%
“…11,13,14 Myocardial protection was provided by topical cooling and intermittent cold crystalloid cardioplegic solution (Kyushu University Solution). 15 The approach to the mitral valve was through a superior trans-septal approach.…”
Section: Operative Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Gore and Associates, Flagstaff, AZ, USA) chordae for mitral valve repair in adults were first reported by David in 1989 and by Frater a year later [1,2]. Since then further studies have reported good mid-and long-term results of mitral valve repair in adults using this technique [3][4][5]. Goretex neochordae are now widely accepted for mitral valve surgery in the adult.…”
Section: Introductionmentioning
confidence: 99%